ANALISIS GUGUS FUNGSI SERTA PENETAPAN KADAR TOTAL FLAVONOID DAN ALKALOID PADA EKSTRAK PAKIS MERAH (Stenochlaena palutris) - Angga Bayu Budiyanto; Wa Siti Arabiya (JURNAL ETNOFARMASI, 2025)
This study aimed to evaluate the effectiveness of three extraction methods (maceration, soxhletation, and reflux) in obtaining bioactive compounds from Red Fern (Stenochlaena palutris), which is known to have therapeutic potential. The methods used included cold extraction (maceration) and hot extraction (soxhletation, reflux) with ethanol solvent, which was chosen because of its ability to dissolve polar and nonpolar compounds. The maceration method produced the highest yield of 15.4002% with extraction for 72 hours without heating, which maintained the stability of the active compounds. In contrast, the soxhletation and reflux methods produced yields of 2% and 10%, respectively, possibly due to degradation of the active compounds due to heating. Phytochemical screening showed the presence of alkaloids, flavonoids, tannins, saponins, steroids, and terpenoids in the resulting extracts. FTIR assay identified various important functional groups such as hydroxyl (-OH), alkanes, and C-O in all extraction methods. and the determination of the total alkaloid content obtained was 1.066335% while the total flavonoid content obtained was 4.652425%. So from the data it can be seen that the total Flavonoid compound is greater than the Alkaloid compound